2016
DOI: 10.1098/rspa.2016.0294
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady solute dispersion in non-Newtonian fluid flow in a tube with wall absorption

Abstract: The theory of miscible dispersion in a straight circular pipe with interphase mass transfer that was investigated by Sankarasubramanian & Gill (1973

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 26 publications
3
37
2
Order By: Relevance
“…Nagarani et al [24] studied the effect of wall absorption on dispersion in Casson fluid flow in a conduit and extended the theory in an annular pipe in the subsequent paper [25]. In recent days, a large number of articles [26][27][28][29] are widely available in the literature to understanding the dispersion process in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Nagarani et al [24] studied the effect of wall absorption on dispersion in Casson fluid flow in a conduit and extended the theory in an annular pipe in the subsequent paper [25]. In recent days, a large number of articles [26][27][28][29] are widely available in the literature to understanding the dispersion process in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, it is observed that the magnitude of −K 0 (t) present study Rana & Murthy [7] (b) (a) increases with β. Similar observations were elaborately discussed in Sankarasubramanian & Gill [6] and Rana & Murthy [7][8][9]. Hence, we have skipped the discussion on K 0 (t) with β and focused mainly on the discussion of the convection coefficient K 1 (t), the dispersion coefficient…”
Section: (B) Exchange Coefficient K 0 (T) and Comparison Of The Presementioning
confidence: 78%
“…In the small arteries, the Peclet number Pe is small; its value becomes large for medium-and large-sized arteries and mass transport mechanisms become advection dominated [8]. The wall absorption parameter β is given values from 0 to 10 2 [6][7][8][9]. In this study, single-phase blood flow is considered for comparison with the two-phase model.…”
Section: (A) Selection Of Parameter Valuesmentioning
confidence: 99%
“…Towards achieving quality mixing in miniaturized devices, the phenomena of diffusion and dispersion stand as the two advantageous mechanisms [12,13]. Hydrodynamic dispersion is a process in which band broadening of a neutral solute occurs because of non-uniformity in the velocity distribution [14][15][16][17][18]. Controlling hydrodynamic dispersion necessarily holds a key towards realizing optimal functionalities of several microfluidic devices of contemporary relevance [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%